(untitled) (International journal of medical sciences, 2026)
Carbon monoxide (CO) is a colorless, odorless, and tasteless gas that poses a serious threat to human health. Because it is undetectable without special devices, it is often referred to as “the invisible killer.” CO poisoning remains a significant public health problem worldwide, particularly during cold seasons when heating appliances are widely used. This article discusses the sources of carbon monoxide, its mechanism of toxicity, clinical manifestations, diagnosis, treatment principles, and preventive measures. Increasing public awareness and implementing safety strategies can significantly reduce morbidity and mortality associated with CO exposure.